YOUTUBE AUTO-TRANSLATION IN SONG LYRICS: TRANSLATION TECHNIQUES, METHODS, AND IDEOLOGIES ON JANJI SETIA BY TIARA ANDINI - Muhamad Saiful Mukminin (Universitas Katolik Widya Mandala Surabaya, 2024)
The YouTube Auto-Translation (YAT) feature represents an innovation in translation technology development. This feature allows for translating songs into other languages by displaying subtitles. The present research aims to investigate the application of translation techniques in translating the song Janji Setia by Tiara Andini using the YAT feature. By analyzing the translation techniques used, it is possible to identify the tendencies in methods and ideologies of translation. The present research employs a descriptive qualitative method with a product-oriented translation approach. Data is collected through listening and note-taking techniques, then transcribed into written form. The researcher listens to the song’s version in Indonesian and records it along with its English subtitles. Data analysis involves data reduction, data presentation, and drawing conclusions. The findings indicate that the YAT feature employs nine translation techniques in translating the lyrics of Janji Setia into English. These techniques are established equivalence, linguistic amplification, compensation, reduction, amplification, adaptation, discursive creation, and literal translation. Based on the translation techniques used, it is evident that the method and ideology of the YAT feature in translating song lyrics are oriented towards the target language with a domestication ideology. This research enriches the understanding of how translation techniques, methods, and ideologies are applied in translating song lyrics using the YAT feature.